Pengaruh Substitusi Tepung Mocaf (Modified Cassava Flour) Pada Pasta Lasagna Terhadap Daya Terima Konsumen - Tiftazani, Ghausi Muhammad; Riska, Nur; Sachriani, Sachriani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the effect of mocaf (Modified Cassava Flour) flour substitution in lasagna pasta on consumer acceptability. This research uses an experimental method which is basically a method to find causes (Santoso, 2020). In this study, two stages were carried out, namely testing to find the best formula for mocaf flour substitution lasagna pasta products and testing consumer acceptance of the lasagna pasta. The experiment was carried out by making mocaf flour substitution lasagna pasta with a percentage of 30%, 40% and 50% as an ingredient to replace some of the wheat flour used in making lasagna pasta. The population in this study was mocaf flour substitution lasagna pasta. The sample in this study was mocaf flour substitution lasagna pasta as much as 30%, 40% and 50%. The data analysis technique carried out by researchers is to add up the results of data from organoleptic testing on somewhat trained panelists. Based on the results of the calculation of the consumer acceptance test and hypothesis testing, it can be concluded that the formula most favored by panelists is fresh pasta lasagna substituted with mocaf flour at a percentage of 30% because in this study it is considered to have better acceptability from the aspects of taste, aroma texture before and after baking, elasticity and stickiness compared to the percentages of 40% and 50%.